2001
DOI: 10.1097/00007890-200109270-00006
|View full text |Cite
|
Sign up to set email alerts
|

Patients at Risk for Development of Posttransplant Lymphoproliferative Disorder: Plasma Versus Peripheral Blood Mononuclear Cells as Material for Quantification of Epstein-Barr Viral Load by Using Real-Time Quantitative Polymerase Chain Reaction1,2

Abstract: Although both PBMCs and plasma were useful as material for EBV-specific RQ-PCR in immunosuppressed patients and nonimmunosuppressed individuals, the specificity of analysis seemed to be higher if plasma was taken for analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
155
4
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(174 citation statements)
references
References 38 publications
11
155
4
4
Order By: Relevance
“…11,16,17 Furthermore, it should be noted here that the value of monitoring EBV DNA load in plasma rather than in whole blood in the transplantation setting is also a subject of controversy. 22,23 In a previous study, 11 we showed high viral loads in all blood compartments (plasma, peripheral blood mononuclear cells, and whole blood) in two patients with proven PTLD, whereas two recent studies 24,25 demonstrated that whole blood was more sensitive for the quantification of EBV DNA in transplant patients than plasma. Moreover, Stevens et al 12 described EBV-associated PTLDs without detection of EBV DNA in plasma, whereas the EBV DNA loads were high in whole blood.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…11,16,17 Furthermore, it should be noted here that the value of monitoring EBV DNA load in plasma rather than in whole blood in the transplantation setting is also a subject of controversy. 22,23 In a previous study, 11 we showed high viral loads in all blood compartments (plasma, peripheral blood mononuclear cells, and whole blood) in two patients with proven PTLD, whereas two recent studies 24,25 demonstrated that whole blood was more sensitive for the quantification of EBV DNA in transplant patients than plasma. Moreover, Stevens et al 12 described EBV-associated PTLDs without detection of EBV DNA in plasma, whereas the EBV DNA loads were high in whole blood.…”
Section: Discussionmentioning
confidence: 94%
“…However, the usefulness of monitoring EBV DNA load in HIV-infected patients to predict a higher risk of AIDS-associated lymphomas is still a matter of debate. 22,23 No significant differences were found between the mean and median of EBV DNA loads in the whole blood of patients with IM, HIV-infected patients, and transplant recipients.…”
Section: Discussionmentioning
confidence: 95%
“…Hakim et al [2007] have found comparable sensitivities and a close quantitative correlation between EBV load in whole blood and peripheral blood mononuclear cells suggesting that a normalization to cell number in cellular specimens may not be necessary. Plasma as material for EBV polymerase chain reaction is favored by several authors [Orii et al, 2000, Niesters et al, 2000, Wagner et al, 2001. In comparison to mononuclear cells the specificity for the diagnosis of EBV lymphoproliferative disease seems to be higher if plasma is taken for analysis as underlined by Wagner et al [2001].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma as material for EBV polymerase chain reaction is favored by several authors [Orii et al, 2000, Niesters et al, 2000, Wagner et al, 2001. In comparison to mononuclear cells the specificity for the diagnosis of EBV lymphoproliferative disease seems to be higher if plasma is taken for analysis as underlined by Wagner et al [2001]. In contrast, the study performed by Hakim et al [2007] demonstrated that whole blood and peripheral blood mononuclear cells are more sensitive than plasma alone when assayed for EBV load.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used plasma or serum because they are readily obtained and handled. Several studies reported that quantifying cell-free EBV DNA predicted the development of PTLD [59,68,69]. However, serum or plasma samples lack cell-associated virus and therefore plasma loads are not correlated with PBMC values [70].…”
Section: Post-transplant Lymphoproliferative Disordermentioning
confidence: 99%